Antifungal activity of selected medicinal plants extract against human pathogenic fungus candida albicans - ARUN KUMAR; VIJAI MALIK; SHRUTI SAINI (International Journal of Pharma and Bio Sciences, 2017)
The present investigation was carried out to observe the antifungal activity of Alstonia scholaris, Argemone maxicana, Datura alba, Solanum nigrum and Solanum xanthocarpum. For this purpose effect of different alcoholic extract concentration was observed on growth performances of Candida albicans on 5th and 7thday. Result shows that alcoholic extract concentrations inhibit radial growth of this fungus. Results also indicate that inhibition of fungal growth increase with the increase in the concentration of alcoholic extracts.